Pteridófitas da região noroeste do Estado de São Paulo, Brasil: Dennstaedtiaceae - Siqueira, Claudia R [UNESP]; Windisch, Paulo G (Sociedade Botânica do Brasil, 1998)
O trabalho faz parte de uma série de estudos sobre pteridófitas da região noroeste do Estado de São Paulo. Os representantes da família Dennstaedtiaceae são encontrados principalmente nas margens das matas ciliares e em barrancos úmidos e sombreados, com exceção de Pteridium que geralmente ocorre em lugares abertos e ensolarados. Ocorrem na região os gêneros Dennstaedtia com duas espécies (D. cicutaria (Sw.) Moore e D. globulifera (Poir.) Hieroni), Lindsaea com três espécies (L. lancea (L.) Bedd., L. quadratigularis Raddi e L. striata (Sw.) Dryand.) e Pteridium com uma espécie e variedade (P aquilinum (L.) Kuhn var. arachnoideum (Kaulf.) Brade). Descrições, ilustrações, chaves de identificação, bem como distribuição geográfica e habitats de cada espécie são apresentados.

This work is part of a series of studies on pteridophytes of the North-western region of the State of São Paulo. The representatives of the family Dennstaedtiaceae are found mainly at the margins of the ciliary forests as well as in humid and shaded ravines, except for Pteridium which, generally occurs in open and sunny places. The genera Dennstaedtia with two species (D. cicutaria (Sw.) Moore and D. globulifera (Poir.) Hieroni), Lindsaea with three species (L. lancea (L.) Bedd., L. quadrangular is Raddi and L. stricta (Sw.) Dryand.), and Pteridium with a species and variety (P aquilinum (L.) Kuhn var. arachnoideum (Kaulf.) Brade), have been found in this region. Descriptions, illustrations, identification keys, geographical distribution, and habitats of each species are presented.
Pteridophytes of the North-western region of the State of São Paulo, Brazil: Dennstaedtiaceae
Keywords: Dennstaedtiaceae; pteridófitas; florística; São Paulo; Brasil; Dennstaedtiaceae; pteridophytes; floristics; São Paulo; Brazil